Integrating water depth to predict the threshold of collapse and recovery of submerged macrophytes for lakes with large depth gradients - Yu, Yexin; Li, Yehao; Wang, Haijun; Su, Haojie; Rao, Qingyang; Liu, Ying; Xie, Ping (Frontiers in Plant Science, 2025)
IntroductionThe nutrient threshold of collapse and recovery of submerged macrophytes have been widely reported for shallow lakes. However, understanding the threshold variation for lakes with water depth (Z) gradients remains limited.MethodsIn this study, based on a field investigation of 9 lakes with varying water depths and nutrient levels in the Yunnan Plateau, southwest of China, we integrated water depth to predict the nutrient threshold of collapse and recovery of submerged macrophytes in lakes.ResultsOur results showed that: 1) Canopy-forming submerged macrophytes, i.e. Potamogeton pectinatus and Myriophyllum spicatum, had a higher resistance to high nutrients and turbidity; 2) Submerged macrophyte species richness had a significantly negative response to water depth, while biomass did not; 3) A multiplication of turbidity (Turb) with water depth provided the best explanation for the collapse and recovery of submerged macrophytes for lakes with large depth gradients compared to the single variables; 4) The thresholds of ZSD/Z were 0.06 for the collapse of submerged macrophytes and 0.53 for the recovery of submerged macrophytes; the corresponding thresholds were 81.6 and 9.92 NTU m for Turb*Z, respectively.DiscussionOur findings on the thresholds of macrophyte collapse and recovery are expected to provide quantitative guidance for lake restoration of diverse water depths.